El obispo Amador Arraiz, divulgador de las obras históricas en latín y portugués de André de Resende - Maestre Maestre, José María (Euphrosyne: Revista de filología clássica, 2009)
This article studies the influence of the Libri quatuor de antiquitatibus Lusitaniae and of the Historia da antiguidade da Cidade de Evora by L. Andreas Resendius in the Dialogos de frey Amador Arraiz, Bispo de Portalegre specifically in Dialogo IV. The research is very significant to establish the authorship of Dialogo IV. The date of publication (1593) of the Libri quatuor de antiquitatibus Lusitaniae makes us think that it was Amator Arraiz rather than his brother Hieronymus who carried out the study and the translation of the afore mentioned Latin work by Resendius. The presence of textual chunks of the Historia da antiguidade da Cidade de Evora leads us to the same conclusion, not only for chronological reasons but for the different nature of the language used in the two versions of the Dialogos (Latin, in the case of the first one written by Hieronymus Arraiz, and Portuguese, for the second one by his brother Amator). Moreover, the comparison of Resendius works - and, above all, of the Libri quatuor de antiquitatibus Lusitaniae - with Dialogo IV puts forth the laudable spreading work of Amator Arraiz and his effort to develop one of the most wonderful monuments of Portuguese literary language.